The best pet ever - Roberts, Victoria (Tiger Tales, 2010)
The little girl wants a pet, but her mother says "We'll see". So the girl tries a rock that she names Fluffy as a pet. Next a glove, a candy wrapper, and a balloon are pets. With imagination, anything can be a pet. But what will be the best pet of all?